Antimicrobial activity in cultures of some xylotrophic basidiomycetes from Azerbaijan - Alimammadova-Husuyeva A.A.; Bisko N.A.; Mytropolska N.Yu.; Gurinovych N.V.; Aghayeva D.N. (Ukrainian Botanical Journal)
Antimicrobial activity of several strains of Laetiporus sulphureus, Phellinus igniarius, and Pleurotus ostreatus against Gram-positive and Gram-negative bacteria Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa was studied. It has been demonstrated that under the influence of ethyl acetate extracts of the culture liquid of L. sulphureus 2780, the inhibition zones of growth of all investigated species of bacteria varied within 7.5–12.0 mm. The extracts of the biomass and culture fluid of L. sulphureus 2780, Phellinus igniarius 2781, and Pleurotus ostreatus 2779 inhibited the growth of Staphylococcus aureus (inhibition zones — 7.5–10.0 mm) and Bacillus subtilis (inhibition zones — 9.5–12.5 mm). The results indicate the potential of the strains L. sulphureus 2780, Ph. igniarius 2781, and P. ostreatus 2779 from the IBK Mushroom Culture Collection as antimicrobial agents against the Gram-positive bacterium Bacillus subtilis.